Carbon mineralization pathways for carbon capture, storage and utilization - Greeshma Gadikota (Nature Portfolio, 2021)
Carbon mineralization is a versatile and thermodynamically downhill process that can be harnessed for capturing, storing, and utilizing CO2 to synthesize products with enhanced properties. Here the author discusses the advances in and challenges of carbon mineralization, and concludes that tuning the chemical interactions involved will allow us to unlock its potential for advancing low carbon energy and resource conversion pathways.